2021
DOI: 10.3390/brainsci11020250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcranial Direct Current Stimulation (tDCS) on Go/NoGo Performance Using Food and Non-Food Stimuli in Patients with Prader–Willi Syndrome

Abstract: Prader–Willi syndrome (PWS) is a neurodevelopmental genetic disorder characterized by multiple system involvement with hypotonia, poor suck with feeding difficulties, growth and other hormone deficiencies, intellectual disability, and behavioral problems with childhood onset of hyperphagia resulting in obesity, if not externally controlled. Transcranial direct current stimulation (tDCS) has been increasingly shown to modulate cognitive and behavioral processes in children and adults, including food-intake beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…These include transcranial direct-current stimulation and transcutaneous vagus nerve stimulation in individuals with PWS, as well as generated information relating to brain regions and function impacted by the PWS diagnosis which require more testing. No specific differences were noted in response to the individual clinical-trial protocols or therapeutic agents related to the PWS molecular genetic classes identified in the PWS participants enrolled in the clinical trials [23,40,[46][47][48][49]58].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These include transcranial direct-current stimulation and transcutaneous vagus nerve stimulation in individuals with PWS, as well as generated information relating to brain regions and function impacted by the PWS diagnosis which require more testing. No specific differences were noted in response to the individual clinical-trial protocols or therapeutic agents related to the PWS molecular genetic classes identified in the PWS participants enrolled in the clinical trials [23,40,[46][47][48][49]58].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been undertaken in multiple studies in humans and can stimulate targeted brain regions and networks to increase or decrease cortical excitability in children or adults. In addition, the dorsolateral prefrontal cortex (DLPFC) is involved in the regulation and processing of food craving and motivation accessible by tDCS [46][47][48].…”
Section: Transcranial Direct-current Stimulation (Tdcs) Clinical Tria...mentioning
confidence: 99%
See 1 more Smart Citation
“…The rationale came from evidence in healthy individuals and in patients with stroke (Fertonani et al, 2010 ; Cattaneo et al, 2011 ; Wirth et al, 2011 ). In the case of PWS, the aim was to enhance prefrontal neural circuit excitability by anodal tDCS with the goal of reducing excessive activity in subcortical structures and, in turn, decreasing hyperphagia (Boggio et al, 2009 ; Bravo et al, 2016 ; Azevedo et al, 2017 , 2021 ; Poje et al, 2021 ). The rationale came from a number of studies in healthy individuals and in patients with substances abuse and food craving (Fregni et al, 2008a , b ; Boggio et al, 2009 ; Goldman et al, 2011 ).…”
Section: From Basic Mechanisms Toward Potential Tdcs Applications In ...mentioning
confidence: 99%
“…Specifically, tDCS has been shown to evoke improvements in response inhibition [28] and decision‐making [29]. For example, faster “Go” reaction time on a food “Go/No‐Go” (GNG) task [30] and improvements in accuracy, mean reaction time, and commission errors on a dual food‐related two‐back GNG task [24] have been observed following anodal tDCS to the right dlPFC in participants with PWS [30] and to the left dlPFC in women [24]. The effectiveness of tDCS may even be improved with the addition of a cognitive task that promotes neuronal activity in the target brain regions [31].…”
Section: Introductionmentioning
confidence: 99%